2016
DOI: 10.1177/0310057x1604400606
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Introducing Unrestricted Access to Sugammadex and Quantitative Neuromuscular Monitors on the Incidence of Residual Neuromuscular Block at a Tertiary Teaching Hospital. An Audit of ‘Real-Life’

Abstract: The influence of introducing unrestricted access to sugammadex and quantitative neuromuscular monitors on the incidence of residual neuromuscular block at a tertiary teaching hospital. An audit of 'real-life'.Residual neuromuscular block (RNMB) is a common phenomenon and has been identified as a significant risk factor for adverse postoperative patient outcome. The outcome of a recent randomised, controlled trial suggests that monitor-guided, sugammadex-based reversal of neuromuscular blocking agents (NMBA) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Therefore, quantitative intraoperative neuromuscular monitoring is strongly recommended to prevent postoperative residual paralysis [ 3 , 39 41 ]. Without such objective monitoring, even the unrestricted use of sugammadex cannot completely eliminate the risk of residual paralysis [ 42 ]. Consequently, the purpose of neuromuscular monitoring is dual: on the one hand, the most effective dose should be administered in order to exclude residual paralysis.…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, quantitative intraoperative neuromuscular monitoring is strongly recommended to prevent postoperative residual paralysis [ 3 , 39 41 ]. Without such objective monitoring, even the unrestricted use of sugammadex cannot completely eliminate the risk of residual paralysis [ 42 ]. Consequently, the purpose of neuromuscular monitoring is dual: on the one hand, the most effective dose should be administered in order to exclude residual paralysis.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, since the response was anonymous, completion bias cannot be excluded. Although we included questions addressing limitations reported in other studies[678910] in order to develop a more complete questionnaire, a validation of the instrument was not performed prior to administration.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple surveys conducted worldwide indicate that neuromuscular blocking drugs and their antagonists are commonly administered without adequate rationalization and monitoring, leading to variable incidence of RNMB. Studies from the United States, Europe,[6] Australia and New Zealand,[78] Italy,[910] Denmark,[11] Morocco,[12] and Brazil[13] suggest that currently, only a small percentage of anesthesiologists monitor neuromuscular function in their clinical practice, even in special patient groups. In addition, the absence of internationally accepted clinical guidelines regarding neuromuscular blockade remains a major problem.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, objective NMM has been shown to decrease the incidence of RNMB and postoperative respiratory complications [35,36]. In addition, it has been reported that an institutional leader who is dedicated to a comprehensive education and implementation plan of objective monitoring can dramatically decrease the number of RNMB and critical respiratory events [42][43][44][45][46].…”
Section: The Introduction Of Objective Monitoringmentioning
confidence: 99%